Wake from a boat on the Kemijoki River - Rovaniemi, Finland - photograph ... - Campbell, Sandy (University of Alberta Library, 2011)
After a boat had passed by, the waves from the wake moved toward the banks. The Kemijoki River flows from northern Finland, joins the Ounasjoki River at Rovaniemi and then flows out to the Gulf of Bothnia near Kemi. ...